Challenging the Centre: Asylum Seekers Encounter Native Citizens - Koski, Pirkko (Nordic Theatre Studies, 2015)
In Paper Anchor (Paperiankkuri) at the Small Stage of the Finnish National Theatre in 2011 a group of actors, dancers, asylum seekers and eventually also stage technicians (re-)enacted the asylum seekers’ stories: how they had fled their home countries, feared for their lives and faced problems in their country of destination, Finland. It brought the spotlight on asylum seekers, who occupy a marginal position in society and made them visible on many levels: they were present in the stories that were told on stage, in the encounter between performers and spectators and in an art institution that has great national significance. The periphery and the centre, in this case the asylum seekers and the native Finns, met in shifting circumstances and also in a way that is characteristic of the theatre: the performers and spectators were simultaneously physically present, whereas the public debate on refugee issues usually takes place in written texts. In Paper Anchor, the asylum seekers also assumed the role of a witness, whereas in official processes they are obligated to defend themselves and search for evidence. The impact of Paper Anchor was largely based on the aesthetic form of the performance. Although the dominant power structures between the centre and the periphery remained untouched, theatre testified to its ability to affect the spectator through the presence of individual subjects and consequently their subject positions. The debate was shifted to differences within a culture instead of between cultures, as Rosi Braidotti writes: “It is the syntax of social relations, as well as their symbolic representation, that is in upheaval.” (Rosi Braidotti, Nomadic Subjects. Embodiment and Sexual Difference in Contemporary Feminist Theory, Columbia University Press, New York 2011, p.8.)